A Review Paper on Machining of Metal Matrix Composite and Optimizing Methods used in Electrical Discharge Machining - Paswan, K.; Chattopadhyaya, S.; Pramanik, Alokesh (2018)
© 2018 Elsevier Ltd. Electric discharge machining is a non-conventional thermal erosion process. In this article investigation has been done on the effect of different reinforcement (carbides, oxides and nitrides), dielectric (kerosene, distilled water and PMEDM) and methods (RSM and GRA) for machining of MMC materials and optimizing the responses. Variation in responses due to all these factors are properly examined and depicted in figures. Result shows that there are various reinforced materials available and different methods have been developed effectively and many more can be. These information and methods can be used to optimize the result according to their requirement.